Life-long learning skills as a basis for individual learning style of university students - Irina L. Smagina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In a current situation of society development, each person should have life-long learning skills, which allow him to be flexible, autonomous, able to adapt to different scenarios of todays unstable reality. These skills can be referred to the category of soft skills, the development of which give the students the opportunity to organize their learning process effectively, and it will also help in forming students individual learning style. Life-long learning skills formed at the university can also be considered as skills oriented to the prospect of further personal and professional development perspective life-long learning skills. Thus, the purpose of this study is to find mechanisms of the development of students life-long learning skills that also help in forming their individual learning style. Using the methods of theoretical, structural-content and comparative analysis, as well as the synthesis of ideas, it was possible to find out that life-long learning skills belong to the category of soft methodological skills, the development mechanism of which is the strategies of independent learning. Moreover, studying the relationship between such concepts as life-long learning skills, universal competencies, individual learning style showed that the development of soft methodological skills of life-long education is the basis for the formation of students individual learning style. As part of the study, it was developed a methodology for teaching students cognitive and metacognitive strategies for independent learning in a foreign language class while working on listening. As the expected results of the application of this methodology, it is assumed that having mastered the strategies and techniques of independent learning, students will be able to deal with the learning material better, which in turn will help to master the competences more successfully, to increase learning motivation and to form students subjective position. As a prospect for further research, we see the development and testing of technology for teaching students the skills of life-long education, with a detailed description of the stages and guidelines for students and teachers.